Issuance Value, Issuance Rating and Life of Sharia Bond on Sharia Capital Market Reaction - Rimi Gusliana Mais; Dea Maharani; Agus Prasetyo (LPPM Universitas Terbuka, 2021)
This study aims to examine whether the value of islamic bonds issuance, rating of islamic bonds issuance, and age of islamic bonds issuance to the capital market reaction. The value of islamic bonds issuance is proxied by sukuk equity ratio, rating of islamic bonds issuance, and age of islamic bonds are used as independent variables. The capital market reaction is proxied by abnormal return as the dependent variable on Companies Issuing Bonds on the Indonesia Stock Exchange. This study uses a descriptive quantitative approach, which is measured using a multiple regression analysis method with Eviews 10. The population of this study is Companies Issuing Bonds on the Indonesia Stock Exchange (IDX) from 2017 to 2019. With a total sample size of 16 companies with the amount of islamic bonds as much as 135. The results of this study prove that (1) The value of islamic bonds issuance has an effect on the capital market reaction, (2) The rating of islamic bonds issuance has an effect on the capital market reaction, and (3) The age of islamic bonds has no effect on the capital market reaction on Companies Issuing Bonds on the Indonesia Stock Exchange 2017-2019.